A cone pressuremeter for soil characterisation in the centrifuge. Issue 1 (March 2007) - Thorel, L.; Gaudin, C.; Rault, G.; Garnier, J.; Favraud, C.
Abstract : A cone pressuremeter for use in the geotechnical centrifuge has been developed by the Laboratoire Central des Ponts et Chaussées (LCPC) based on the in-situ Ménard pressuremeter. It includes a pressuremeter probe, 20 mm long, mounted on a 10 mm diameter metallic shaft. Sensors measure the pressure inside the probe and the volume injected, leading to the determination of the limit pressure PL and the pressuremeter modulus EP, using a procedure similar to the one used for the in-situ Ménard pressuremeter. The technical aspects of the device are presented in detail as well as the testing procedure and the corrections required by the apparatus. Some preliminary results for tests performed in Fontainebleau sand and comparisons with cone penetrometer results are also presented. The correlation between the tip resistance and the limit pressure is conclusive, demonstrating the feasibility of such tests and the validity of the results.